In vitro activity of aztreonam combined with tobramycin and gentamicin against clinical isolates of Pseudomonas aeruginosa and Pseudomonas cepacia from patients with cystic fibrosis. - Bosso, J A (1987)
The in vitro activity of aztreonam combined with tobramycin and with gentamicin was assessed in 78 clinical isolates of Pseudomonas aeruginosa and 11 clinical isolates of Pseudomonas cepacia from patients with cystic fibrosis. Synergy was detected in 56.4% of P. aeruginosa isolates and 60% of P. cepacia isolates with the aztreonam-tobramycin combination and in 49.3% of P. aeruginosa isolates and 81.8% of P. cepacia isolates with the aztreonam-gentamicin combination. No antagonism was observed. These combinations merit clinical evaluation in the treatment of patients with cystic fibrosis.